SIMILARITIES AND DISTINCTION PATTERN RECOGNITION OF PHYSICAL FITNESS RELATED PERFORMANCE BETWEEN AMATEUR SOCCER AND FIELD HOCKEY PLAYERS: Life Sciences-Biology - MOHAMAD RAZALI ABDULLAH; RABIU MUAZU MUSA; NORLAILA AZURA KOSNI; AHMAD BISYRI HUSIN MUSAWI MALIKI; MOHD SYAIFUL AKMAL ABDUL KARIM; MAINUL HAQUE (International Journal of Life Science and Pharma Research, 2022)
This study aims to identify the components of physical fitness related performance pattern of similarities and variation among soccer and hockey amateur players. Amateur soccer (N=31) and hockey players (N=31) were recruited from Johor sports school, Malaysia. Standard battery fitness tests were conducted, and principle component analysis (PCA) was employed to identify the most significant physical related performance components and to determine the similarities and variations of the components between the two sports. The PCA after varimax rotation revealed two varifactors (VF) for both soccer and hockey (eigenvalues>1). The VF with higher positive factor loadings contains four main components which include vertical jump, standing broad jump, sit and reach and velocity of agility while the other VF indicated three components containing maximum pushups, sit–ups and VO2max suggesting the need for lower body strength and endurance for soccer players. Similarly, for hockey, the first VF included speed, vertical jump, standing broad jump and agility. The second VF contained maximum pushups, maximum sit-ups, and VO2max recognizing the requirement of lower limb power and core body strength. Identifying physical fitness patterns for amateur soccer and hockey players might help the coaches to structure training programs to suit the need for each sport.